Healthy Living: Exercise and Diabetes - Sergio Romero; Linda B. Bobroff (EDIS)
Staying active is one of the best things you can do for your health. Regular physical activity can help you control your blood glucose levels, reduce body fat, and decrease your risk of heart disease. Staying active also can help you sleep better, improve posture and balance, maintain independent living, and improve quality of life. Here are some tips to help you create a fun and healthy exercise program. Start today! This revised 2-page fact sheet was written by Sergio Romero and Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, February 2011.